Penelopes of the modern era: feminine and masculine freedoms in Ivan Franko’s novel "For the Home Hearth" and Milan Begović’s "Giga Barićeva" - Tatarenko, Ałła (Porównania, 2024)
In this study, we examine the peculiarities of interpreting the image of Penelope in the novel For the Home Hearth by Ivan Franko, a luminary of Ukrainian literature, and in the novel Giga Barićeva by Milan Begović, one of the most famous Croatian modernists. The emancipation of women and the change in their role in society led to a modern interpretation of mythological characters: in the mirror of the new era and its values, their stories acquire new meanings and become indicators of the modern worldview and its challenges. The image of Odysseus’s faithful wife is one of them. Franko and Begović unambiguously emphasize the different interpretations of freedom regarding the behavior of men and women, and the acceptance of their inequality by society. A parallel reading of Ivan Franko’s and Begovic’s novels allows us to note typological parallels and authorial findings in the interpretation of the Penelope image, which can serve as interesting material for a study that will generalize the functioning of this image in European modernist literature.